Prediksi Fluktuasi Muka Air Tanah Untuk Pengembangan Komoditi Lahan Gambut Berwawasan Lingkungan - Melani Humairoh; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In Siak regency, there are 10,000 hectares OF TORA land (Land object of agrarian reform) which is a peat area and 92% of them are deep peat. An area of 2,000 Ha of the total number of TORA land is at HGU 07. The Local Government of Siak Regency will manage the peatland productively in economic terms but does not damage the peat ecosystem. Based on PP RI number 57 year 2016 on protection and management of peat Ecosystem, the peat ecosystem with cultivation function is declared to be damaged when water level in peat land more than 0.4 meters below the peat surface at the linking point. The purpose of this research is to predict the fluctuation of groundwater in consideration to support the efforts to optimize the development of environmental commodities peatland in Siak Regency. The effort to maintain water level above 0.4 m is so that PP RI No 11 Tahun 2009, peat is kept in wet conditions for carbon emissions and the threat of land and forest fires due to drying of land can be reduced. Ground water advance fluctuations are predicted using linear regression methods. The results showed that the result of the calculation obtained the value of efficiency Of Determination In the highest dwrain analysis of 3 months with a data length of 0.5777. The prediction of ground water advance fluctuations in May – December means that water depth is not in accordance with government regulations that set a water level height of less than 0.4 m below ground level. Alternative commodity can live with government regulation if planted in surplus month, namely February to April.Keywords : hydrology, water balance, peat land, regression analysis, water level